2007
DOI: 10.1080/14786410701371553
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and biological variations ofEpidendrum mosenii: quantification of 24-methylenecycloartanol using gas chromatography

Abstract: Epidendrum mosenii is a Brazilian medicinal plant, traditionally used to treat infective and dolorous processes. The present article reports a comparative study of the chemical and pharmacological aspects of different parts and seasons of this plant. The results demonstrate that 24-methylenecycloartanol (1), one of the main active principles present in this plant, is located practically in all the parts and during all seasons, but it is much more concentrated in the stems when collected in spring and summer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Three esterified tetracyclic triterpenes of compound 2 were recently reported from the dichloromethane extract of the roots of E. retusa : 24-methylenecycloartanyl formate, 24-methylenecycloartanyl 2′ E ,4′ E -decadienoate, and tirucalla-7,24-dien-3-yl 2′ E ,4′ E- decadienoate [ 27 ]. Biologically, compound 2 was reported to prevent diet-induced obesity in the liver through GIP-dependent and GIP-independent mechanisms [ 28 ]. Compound 2 was additionally reported to exhibit anti-inflammatory activity [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three esterified tetracyclic triterpenes of compound 2 were recently reported from the dichloromethane extract of the roots of E. retusa : 24-methylenecycloartanyl formate, 24-methylenecycloartanyl 2′ E ,4′ E -decadienoate, and tirucalla-7,24-dien-3-yl 2′ E ,4′ E- decadienoate [ 27 ]. Biologically, compound 2 was reported to prevent diet-induced obesity in the liver through GIP-dependent and GIP-independent mechanisms [ 28 ]. Compound 2 was additionally reported to exhibit anti-inflammatory activity [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…24-methylene-cicloarta nol, dichloromethane extract [7], methanolic extract [18] and phenanthrenes [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…A similar traditional use to alleviate pain is referred to China for the stems of E. mosenii [20], a related species on which pharmacological testing proved a strong anti-nociceptive effect [18][19][20]. Laboratory tests demonstrated that a dichloromethane extract, 24-methylene-cicloartanol and phenanthrenes were responsible of this action [19][20][21].…”
Section: As Far As Their Ethnobotany Villagers Usementioning
confidence: 99%
“…Além destes, foram ainda identificados duas substâncias fenólicas, identificadas como dihidroestilbenos 4,5´-dihidroxi-3,3´-dimetoxi-dihidroestilbeno (49) e 4,3´,5´-trihidroxi-3-metoxi-dihidroestilbeno (50), os quais exerceram propriedades analgésicas relevantes em camundongos (ROSA, 2005). Numa avaliação da composição química em relação à variação sazonal, observou-se que 48 está presente em todas as partes da planta, e durante todas as estações do ano, porém a maior concentração foi evidenciada nos caules coletados na primavera e no verão (ROSA et al, 2007). NIERO et al, 1999NIERO et al, , 2002.…”
Section: Calophyllum Brasiliense Camb (Clusiaceae)unclassified